EAZY PASSPORT SOCIALIZATION, IMMIGRATION SERVICE INNOVATION, AND IMMIGRATION POLYTECHNIC BOARDING SCHOOL IMPLEMENTED BY IMMIGRATION OFFICE CLASS II BORDER CONTROL PEMATANG SIANTAR - Faridh Al Wajidi; Karina K; Wisnu Widayat (Jurnal Abdimas Imigrasi, 2021)
At the time of the implementation of LATJAPURA conducted by the Immigration Polytechnic cadets throughout Indonesia, it became commonplace for every cadet to participate in the implementation of socialization activities held at the immigration office where the cadets actively participated in LATJAPURA. The implementation of this LATJAPURA activity provides an opportunity for the Immigration Polytechnic Cadets to perform community service as a tangible form of contributing to the Indonesian people. One form of community service carried out by the Immigration Polytechnic Taruna in the city of Pematang Siantar is the socialization of Eazy Passport. The purpose of this socialization is to introduce the latest services of the Immigration Office Class II TPI Pematang Siantar in the form of Eazy passports and service innovations to provide convenience to applicants for immigration services. In addition, this activity is also to introduce the Immigration Polytechnic service bond school to the public to increase the existence of the Immigration Polytechnic in Pematang Siantar City.